The Decision of Prospective Students to Choose A Vocational College: The Role of the Marketing Mix and Image - Wahyu Rafdinal; Iwan Mulyawan; Cahaya Juniarti; Sharnuke Asrilsyak (Faculty of Economics, Universitas Sriwijaya, 2020)
This study aims to analyze the students' decision in choosing a vocational college which is influenced by the marketing mix strategy of vocational colleges and image. The sampling technique was purposive sampling, with a total of 200 respondents. The analysis technique used was SEM PLS. Results showed that the marketing mix strategy of the vocational colleges could influence the decision to choose a vocational college through the image of vocational college. The image directly influences the decision to choosing a vocational college. Education services, education costs, promotions, locations, quality of lecturers and staff, processes, and campus environments support in creating the image and decisions to choose a vocational college.